Biogas Technology as an “Engine” for Facilitating Circular Bio-Economy in Denmark—The Case of Lolland & Falster Municipalities Within Region Zealand - Lybæk, Rikke; Kjær, Tyge (Frontiers in Energy Research, 2021)
This paper investigates how biogas technology can facilitate the deployment of municipal circular bio-economic solutions within the energy and agrarian sectors in Denmark. The emphasis is on regional climate policy and existing biogas technology concepts, within a decentralized energy market located in the Southern part of Zealand. The case analysis will identify how such technology can be utilized as a lever for future ‘extraction-activities’, as for example protein, wax and furfural substrates. Within Falster & Lolland Municipalities, it is identified that 800.000 tons of animal manure is readily available for biogas production, just as 880.000 tons and 220.000 tons of unused beet tops and residual cereal straw could be feed to biogas facilities as for example co-silage materials. With a potential gas yield of approximately 897.000 MWh, composed by the crop residues alone, the challenge is how to utilize such resources the most efficient when addressing future needs for bio-products and high value materials and energy. Through the lens of Circular Bio-Economy (CBE) this paper addresses three themes, by which biogas technology can become an ‘engine’ for future bioenergy solutions, where cascading activities and use of side-streams are developed; a) production of biogas by means of local agricultural residues (beet tops, residual straw and animal manure), combined with b) ‘extraction-activities’ as furfural and wax from straw, as well as protein from beet tops. Besides this c) opportunities for upgrading the biogas and distribute it on a natural gas network, hereby enlarging the supply market for energy services from the biogas plant and facilitate development of a more ‘integrated energy system’, currently being promoted by the European Commission. The paper concludes on a step-by-step approach to utilize biomass residues more efficiently in the light of the CBE concept and cascading approach, and the available biomass resources within the specific case area addressed.